Impact of crystallography at Ni/NiAl interfaces on the nucleation of Ni3Al. (15th April 2021) - Seyring, M.; Rettenmayr, M.
Abstract: Early stages of phase formation at (Ni)/NiAl interfaces with different crystallographic configurations were studied. As opposed to earlier work, macroscopic diffusion couples and a low annealing temperature of 650°C were applied. The morphology of the newly forming Ni3 Al phase, its crystallographic relationships to the different (Ni)/NiAl interfaces and the growth kinetics of Ni3 Al were evaluated with appropriate statistics combining EBSD with STEM EDX. The Ni3 Al phase forms in two layers and mainly grows into the NiAl phase, establishing a specific crystallographic relationship with respect to the adjoining phases. The majority of Ni3 Al grains growing into the NiAl phase maintain Kurdjumov-Sachs orientation relationships. The grains in the second Ni3 Al layer mostly grow in a near cube-on-cube orientation relationship (misorientation < 15°) towards the (Ni) phase. The formation of large Al enriched (Ni) grains at the (Ni)/Ni3 Al interface is observed and interpreted as diffusion induced recrystallization. Graphical abstract: Image, graphical abstract